Didactic innovation for the understanding of the concept of vacuum in hydrostatics - Molina-Jiménez, Franklin (2020)
This article describes a proposal of didactic innovation aimed at improving the understanding of the concept of vacuum. The concept of vacuum that is studied in the hydrostatic branch of physics, constitutes one of the most complex and important topics to understand, since it is involved in many activities that the human being develops, from the fundamental process of breathing, to the one of generating numerous scientific and industrial advances. The total absence of matter in a given place is called a vacuum, and it has been analyzed in several ways, mainly in an experimental way. However, the present proposal is aimed at studying it from a theoretical point of view and verifying its existence in a practical way, through the application of the didactic technique of the question-answer and the group research strategy in the laboratory, respectively. The research was developed under a quantitative, quasi-experimental, inductive process in which thirty-three students of the Pedagogy of Experimental Sciences, Mathematics and Physics Career took part. They worked in two moments, in which it was established that the average percentage of understanding of the subject analyzed in the pre-test and post-test increased from 44. 70% to 79. 55%, allowing us to intuit that the use of the didactic innovation proposal, based on the application of the didactic technique questions and answers and the laboratory research strategy, led to a better understanding of the concept of vacuum, in addition to verifying how it influences our daily work.